Prófétai emóciók. Megjegyzések az ószövetségi prófétaság antropológiai aspektusaihoz - NÉMETH, Áron (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2019)
Prophet’s Emotions. Notes on the Anthropological Aspects of Old Testament Prophets. The current study is part of the recent discourse of Old Testament Anthropology, in which feelings, affects, and emotions play a prominent role. In particular, Paul Kruger and Andreas Wagner's approaches and observations have given new impetuses to this research area. My study on the emotions of prophets is situated at the crossroads of the Old Testament emotion research and of the Old Testament prophecy studies. Reflecting on the newer achievements, I examine the description and nature of emotions appearing in prophetic books and in biographies of Old Testament prophets, surveying their possible characteristics. After a brief overview of the research history (1.), the study first deals with the Old Testament concept of emotions in general (2.), then specifically examines three issues of prophetic emotions (3.): how do the emotions of God and the emotions of the Prophet relate to each other? (3.1.); how does the so-called “container-metaphor” appear in context of prophetic emotions? (3.2.); how does emotion and communication relate to each other in the symbolic acts of prophets? (3.3.)